MIDDLE-AGED WOMEN IN POLAND AS A SEGMENT OF TOURIST SERVICES RECIPIENTS - Balińska, Agata (Acta Scientiarum Polonorum. Oeconomia, 2019)
The aim of the article is to present middle-aged women as a segment of recipients on the tourism services market. The article characterizes women’s tourist activity. The available statistical data was reviewed. A survey (hand-out survey) was also conducted on a non-random sample of 155 women. The following research problems were used in empirical studies: What are the reasons for women giving up tourist trips? What form of organization and length of trips do the respondents prefer? Is there a relationship between the respondents’ ability to drive a car and their tourist activity? In whose company do women usually go? What goals decide about undertaking tourist activity and which factors have the greatest impact on the organization of a tourist trip? What is the dream tourist trip of the respondents? The research allowed to determine the ways of spending time preferred by women during tourist trips. Women willingly participated in domestic and foreign tourist trips. They usually left with their family or partner, and the main reason for the trip was the desire to entertain, get to know interesting places and rest. Factors that were most important for the respondents were the weather, leisure places and company. The price was definitely less important.